Zmiany koryta Noteci w jej środkowym odcinku - Kaniecki, Alfred; Ptak, Mariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
The paper analyses the changes in middle course of the Noteć River channel i.e. from Nakło to Ujście. The research was carried out by means of the cartographic method surveying environmental changes. Based on the cartographic material from four different periods of time, the occurrence of considerable changes was determined in the period between the second half of the 18th century and the beginning of the 21st century. The observed transformation was attributed mainly to the anthropogenic factors, including any hydrotechnical works related to e.g. the river’s regulation and drainage works in the river valley. Such activities are aimed at a more efficient use of the Noteć River for economic purposes.
Keywords: environmental changes; rivers; Noteć River; human pressure